Analisis Dampak Sosial Ekonomi Pembangunan Bendungan Kuwil Kawangkoan Bagi Masyarakat di Kabupaten Minahasa Utara - Tampenawas, Maykel Alexander; Mustopa , Opa; Rompas, Jufry; Kumaat, Lusye C. (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research aims to analyze the socio-economic impact of the construction of the Kuwil Kawangkoan Dam on the community in North Minahasa Regency. In collecting data, this research used a qualitative approach with the snowball sampling method to obtain the information needed according to applicable scientific norms. The data analysis technique used in this research is inductive data analysis where the collected data is then processed and used as specific facts, and then general conclusions are drawn. The results of this research show that the existence of the Kuwil Kawangkoan Dam after operation has had a positive impact on the community in North Minahasa Regency, especially the community in Kuwil Village and Kawangkoan Village. This can be seen from the daily activities of residents as well as information obtained from trusted sources.